The age of AI and our human future - Kissinger, Henry 1923-2023; Schmidt, Eric 1955-; Huttenlocher, Daniel P. (Little, Brown and Company, 2021)
Where we are -- How we got here: technology and human thought -- From Turing to today--and beyond -- Global network platforms -- Security and world order -- AI and human identity -- AI and the future
Keywords: Artificial intelligence; Social change; Technology / Social aspects; Artificial intelligence / Philosophy; Artificial intelligence / Social aspects; Artificial intelligence / Forecasting; Artificial intelligence; Forecasting; Artificial intelligence; Philosophy; Artificial intelligence; Social aspects; Technology; Social aspects